PREDATOR-PREY ASSOCIATION AMONG SELECTED ARTHROPOD SPECIES IN THE CROPLAND OF MIXED-CROP ZONE (MCZ) AND COTTON-WHEAT ZONE (CWZ) - S. A. Rana; T. Ruby; N. Rana; M. Afzal; M. Mahmood-ul-Hassan; M. J. I. Siddiqui (Journal of Animal and Plant Sciences, 2012)
Wheat, brassica and fodders (maize, sorghum and alfalfa) were sampled for various arthropod taxa in the mixed-crop (MC) and cotton-wheat (CW) zones of Punjab and predator- prey densities were calculated. Line graphs of predator-prey ratio (p/p) in eight monthly samples were plotted for each predator and its prey species. The most linear horizontal pattern thus obtained revealed an association of a predator to its prey(s). Significance of the association was ascertained by simple linear regression on the relative abundances of both the groups. Findings are helpful in applying a species-specific biological control in nature.
Keywords: Croplands; Arthropods; Predator-prey relationship.